Perlindungan Hukum dan Kebebasan Berserikat dalam Konteks Organisasi Kemasyarakatan di Era Digital - Assidiqi, Rohmatullah; Sujono (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The development of information and communication technology has had a significant impact on the way community organizations (ormas) carry out their activities, including in utilizing the freedom of association guaranteed by Article 28E paragraph (3) of the 1945 Constitution. The use of social media and digital platforms by ormas opens up opportunities to expand the reach of communication, rally support, and convey aspirations more widely. However, behind these benefits, there are serious legal challenges, such as misuse of social media, the spread of hoaxes, criminalization of opinions, and lack of protection of organizational data and privacy. This study aims to examine the implementation of legal policies that support freedom of association for mass organizations in the digital era and identify challenges and solutions for data protection and privacy of mass organizations. Using normative legal methods, this study analyzes relevant regulations, such as Law No. 27 of 2022 concerning Personal Data Protection, Law No. 17 of 2013 concerning Mass Organizations, and Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE). The results of the study show that legal regulations in Indonesia have not fully accommodated the needs of mass organizations in the digital era. There is still a legal gap regarding guidelines for the use of social media by mass organizations and adequate data protection. To overcome this challenge, it is necessary to update regulations that support digital activities of mass organizations, digital literacy training for mass organization administrators, and the application of security technology to protect organizational data and privacy. This research is expected to contribute to the development of better legal policies and practices in supporting freedom of association in the information technology era.